ECONOMIC ADJUSTMENT POLICIES & STRUCTURAL CHANGE AND ITS IMPACT IN AGRICLTURAL POVERTY IN ECONOMIES OF DEVELOPING STATES - Alaa M. Abdullah (Mesopotamia Journal of Agriculture)
The importance of the paper defines that economic adjustment policies and structural change have a deep impact on economic development and agricultural poverty in the future of development economies .Studies and papers have tackled various reflections of these policies upon economic of agricultural developing states .Therefore ,the problem comes to confirm that these reflections might be translated at the end into the fact that the impact in levels of agricultural poverty .The paper aims at studying this relation by answering the following question :Can the programs of economic adjustment and agricultural change be fulfilled without making great problems for the poor ?How can these programs be able to improve the life of the poor for a long- term by depending on the hypothesis which says that economic policies have not created these effects in the rate of agricultural product and in the form which create significant effects in the direction of elevating rates of agricultural poverty through eliminating the variance in distributing agricultural lands .The study has limited a selected sample from developing states of the year 2004 .Throughout the study ,results of standard and statistical analysis were significant and the relation between the rate of agricultural growth and Gini indicator inside the agricultural sector as being dependent variant .This means that the advantages of growth means that the advantages of growth are not distributed equally for there was no clear relation between growth and poverty ,considering that low levels of variance should have been of different effects in growth in comparison with high levels of variance .For this reason ,each state must face a certain level of variance and degrees of variance differ across various states by depending upon structural factors .Therefore ,achieving sustainable growth to be distributed equally is considered as a basic factor in decreasing poverty levels .